Integrasi Musik Tradisional Mondreng dalam Pendidikan Budaya dan Islam: Pendekatan Pembelajaran berbasis Kearifan Lokal: A LOCAL WISDOM-BASED APPROACH - Sarjoko Sarjoko; Sunarto Sunarto; Suharto Suharto; Djuli Djatiprambudi (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
For strengthen identity participant educate and maintain wisdom local, Islamic education and culture local must integrated. Music, art traditional Blitar, has mark social, religious and educational which can implemented in learnin . Research objectives This is for learn How music mondreng can used in Islamic education and culture with use based approach​ wisdom local. Qualitative methods with approach ethnopedagogy used, which involves observation, interviews, and research documentation to practitioners education and actors art. Research results show that integration music mondreng can increase understanding participant educate about values Islam like togetherness, spirituality, and ethics. This can also increase involvement participant educate through experience learning directly. Because learning rooted in culture local, that more contextual and meaningful. As conclusion, music mondreng functioning with Good as tool for integrate Islamic education and culture. Strengthening draft ethnopedagogy based art local is benefit theoretical from study this. Meanwhile that, the benefits practical from study This is a learning model applicable based experience. One of the invention new in study This is merger learning based experience to in framework Islamic education through practice music traditional in a way direct.